A first genetic linkage map of the blue mussel Mytilus edulis - Lallias, Delphine; Hecquet, Céline; Boudry, Pierre; Lapegue, Sylvie; Beaumont, Andy (International Triennial Meeting Aquaculture 2007, 2007)
The blue mussel, Mytilus edulis, is widely distributed in the northern hemisphere, from the White Sea to the Atlantic coast of southern France, and is an economically important species (1 million tons per year, FAO, 2002). At present however, little domestication has been achieved with bivalves, in contrast to agricultural crops, livestock and horticultural species like tomatoes, where selection and production is entirely controlled by man. For bivalves, despite their economic importance, no lines with selected characteristics have been taken to the production scale. There is therefore a need to make up for lost time. Our interest in genetic mapping sprang from some results showing a genetic component to some economically important traits like growth and survival. It was therefore primordial to establish a genetic linkage map in order to better understand the heritability of these traits. The genetic map will provide a framework for the localization of loci linked to the traits, so as to identify QTLs.